Motivation towards learning english fostered by the implementation of a didactic sequence mediated by the use of the Metroidvania Video Game Hollow Knight (2022)
The present research project aims to measure the motivation level of a group of students from an English course at Icesi University by using a didactic sequence mediated by the use of a Metroidvania Video Game as the main engagement element for learning the second language. In order to do so, this paper recovers the different perspectives of the students and the researcher while teaching and learning to use a video game, analyzing how the motivation is promoted and making the comparison among other papers with similar objectives but using different tools and games. Among the findings, a description of the way in which motivation was positively influenced using a didactic sequence mediated by the use of the Metroidvania videogame Hollow Knight through their respective testimonies and information gathered by the researcher while applying the activities proposed for every stage of the experience.